Benefits of Implementing ISO 45001 Occupational Health and Safety Management Systems and Implementation Suggestion in the Defense Industry: A Literature Review - Malinda, Agung; Soediantono, Dwi (AGUSPATI Research Institute, 2022)
The purpose of this article is to explore the benefits of implementing ISO 45001 Occupational Health and Safety Management System in various industries and to provide suggestions to be applied to the defense industry. The method of writing this article is a literature review, namely reviewing by collecting, understanding, analyzing and then concluding as many as 30 international journal articles about ISO 45001 Occupational Health and Safety Management Systems published from 2015 to 2021 regarding the implementation of ISO 45001 Occupational Health and Safety Management Systems in various industrial sectors. and the defense industry. The analysis used was 27 content analysis of journal articles. The results of the literature review analysis state that ISO 45001 Occupational Health and Safety Management System has direct benefits, such as increasing its ability to respond to regulatory compliance issues, reducing overall incident costs, reducing downtime and operating interruption costs, reducing insurance premium costs, reducing absenteeism and employees and turnover rate, Recognition for having reached international standards. ISO 45001 improves the effectiveness of work accident control by implementing a comprehensive OHS management system. ISO 45001 hopes that by controlling the OHS Management System it is able to support SMK3 in all forms of organization so that ISO 45001 Occupational Health and Safety Management System is recommended to be applied in the defense industry.